Chronicles of Narnia. The voyage of the dawn treader [videorecording (DVD)] - Apted, Michael; Swinton, Tilda; Poulter, Will; Markus, Christopher; McFeely, Stephen; Lewis, C. S. (Clive Staples), 1898-1963 (Twentieth Century Fox Home Entertainment, 2011)
When Lucy and Edmund Pensive, along with their cousin Eustace, are swallowed into a painting and transported back to Narnia, they join King Caspian and a noble mouse named Reepicheep aboard the magnificent ship The Dawn Treader. The courageous voyagers travel to mysterious islands, confront mystical creatures, and reunite with the Great Lion Aslan on a mission that will determine the fate of Narnia itself!